A revista Ciência Hoje das Crianças e o discurso de divulgação científica : entre o ludicismo e a necessidade - Baalbaki, Angela Correa Ferreira (2010)
This research is chiefly aimed at investigating the functioning of the scientific popularization discourse for children. Its theoretical-methodological background is the French Discourse Analysis, as conceived by M. Pêcheux. The work has been developed upon an analysis of clippings from sections of issues of the periodical Ciência Hoje das Crianças a publication by Instituto Ciência Hoje and theoretical texts that address the theme. An analysis is developed in order to elicit the images projected in the subject-positions that operate in this discourse. The scientific popularization discourse for children is considered to be an effect of senses between the popularizer, the scientist and the reader (child and teacher). It is a discourse constituted by four orders, namely: science, everyday life, media and teaching. Working in-between the different discourses, the popularization promotes a gesture of interpretation that produces a certain reader effect: the child, or better saying, the image of a child is taken as a subject-to-be. An analysis of the terms child and scientific popularization is carried out to investigate the nets of senses that make up that discourse. Notions such as the categories of child, ludicism and demand discourse were proposed in an attempt to understand the constitution of senses of child for scientific popularization. In this discourse, the set of images related to amusement is tied to the scientist profession, that is to say, to a socially prestige occupation. As a consequence, there follows an imaginary construction of a promising future for the scientists-to-be.